SEBEŞUL, DE LA ORAŞ REGAL LA ORAŞ EUROPEAN (PANGEEA, 2025)
Sebes-city, from royal city to european city. Sebers city, located at the intersection of principal national and European road, has nearly 800 years documentary age. In his existence the town known periods of prosperity and decay, but was always an important handicraft and commercial center, with a very strong German community. Thuis paper is an overview of the main features tried and historical moments of Sebes.